New record of Lysmatella prima Borradaile, 1915 (Crustacea, Caridea, Lysmatidae) from the Arabian Sea, Southwestern India - Pillai, S. Lakshmi; Maheswarudu, G.; Thomas, Jinesh; Ragesh, L.; Sreesanth, M.; Jose, Josileen; Chakraborthy, Rekha Devi (Zootaxa, 2019)
Here we report a new record of the caridean shrimp Lysmatella prima Borradaile, 1915 in the Arabian Sea off southwest coast of India. L. prima is the only known species under the genus Lysmatella (Borradaile, 1915). The species was recorded a century back from the Andaman Sea, Bay of Bengal. During a survey in our research vessel, a single specimen obtained from a depth of 30 m (9o25’72” N 76o12’77” E) is described and illustrated with photographs. This record extends the known distribution of the species in the Indo Pacific region.